MANAGEMENT FISIOTERAPI PADA KASUS OSTEOARTHRITIS KNEE BILATERAL DI RSUD PANDANARANG BOYOLALI - Novita Sri Wulandari,; Taufiq Eko Susilo,; Nur Widya Pradana, (Jurnal Cakrawala Ilmiah, 2025)
Introduction: Osteoarthritis (OA) is the most common joint disorder and usually affects the hip, knee, hand and foot joints. Infrared (IR) is a physiotherapy modality that is often used to treat low back pain. Infrared (IR) radiation can increase blood flow and relax tissue so that it can reduce pain and maximize functional activity. TENS is the generic name for afferent nerve fiber stimulation methods designed to control pain. Strengthening exercise is a strengthening exercise performed on muscles or muscle groups that have decreased muscle strength. Stretching exercise is a physiotherapy action, where patients can do it themselves at home, which is an exercise therapy to prevent neck pain complaints from getting worse. Objective: To determine the physiotherapy management in cases of bilateral knee osteoarthritis. Method: Patients were given infrared, Tens, strengthening, stretching for 4 weeks 3x meetings with doses 3 times in 2 weeks each session 10-15 minutes. Results: evaluation was carried out using Range Of Motion (ROM), Manual Muscle Testing, Numeric Rating Scale. Conclusion: After being given intervention in the form of IR, TENS, strengthening and stretching 3 times in 2 weeks, quite significant changes were obtained.